2020
DOI: 10.7759/cureus.10553
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neoplasia in Colonic Wall Thickening Detected via Computerized Tomography

Abstract: Introduction Colonic wall thickening (CWT) is frequently observed incidentally via abdominal computerized tomography (aCT). Although the general approach to evaluating incidental CWT is a colonoscopic examination, there is a lack of definitive recommendation guidelines. Thus, we aimed to determine neoplasia rates and identify the factors predictive of neoplasia via colonoscopic examinations of patients with CWT incidentally diagnosed via aCT. Methods We retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In particular, splenic enlargement can be observed in 50%-87.9% colon cancer patients treated with oxaliplatin-based ChT with 31% median change of spleen size [ 87 ]. This finding seems to be a surrogate of oxaliplatin-induced SOS, above mentioned among ChT-induced liver injuries, that can be complicated by thrombocytopenia, which has been confirmed to be higher in colon cancer patients treated by oxaliplatinum and developing splenomegaly after ChT [ 87 ]. Thus, this imaging feature encountered in follow-up imaging examinations of oncology patients may be a warning sign in terms of developing SOS.…”
Section: Imaging Findingsmentioning
confidence: 99%
“…In particular, splenic enlargement can be observed in 50%-87.9% colon cancer patients treated with oxaliplatin-based ChT with 31% median change of spleen size [ 87 ]. This finding seems to be a surrogate of oxaliplatin-induced SOS, above mentioned among ChT-induced liver injuries, that can be complicated by thrombocytopenia, which has been confirmed to be higher in colon cancer patients treated by oxaliplatinum and developing splenomegaly after ChT [ 87 ]. Thus, this imaging feature encountered in follow-up imaging examinations of oncology patients may be a warning sign in terms of developing SOS.…”
Section: Imaging Findingsmentioning
confidence: 99%
“… 16 found four subjects with neoplasia that was localized in all cases, while Karacin et al . 7 showed that 63% cases of localized CWT had neoplasia and that focal and asymmetric CWT are independent risk factors for neoplasia. In our study, even though localized CWT did not have a strong predictive value based on the ROC curve, it was found to be independently associated with CRC based on our multivariable logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Previous studies have shown an incidence of 7-21% malignancy rate in patients with CWT. [5][6][7][8][9] No clear consensus exists to date to address the role of colonoscopy in patients with CWT. Some previous studies have suggested performing colonoscopy in these subjects 10,11 but the results remain conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation